How does the tourism and hospitality industry use artificial intelligence? A review of empirical studies and future research agenda - Saydam, Mehmet Bahri; Arici, Hasan Evrim; Koseoglu, Mehmet Ali (Routledge Journals, Taylor & Francis Ltd, 2022)
In response to the increased interest in artificial intelligence (AI) and service robotics within tourism and hospitality (T&H) research, the current study examined 123 articles thematically to determine how AI is defined and which themes are most associated with the phenomena. Several journal articles on AI were extracted and analyzed using bibliometrics (citation and co-citation) and content analysis to uncover the salient themes. We first reviewed the emergent definition of AI and its relevant themes. Then, we presented the methodology and reported quantitative bibliometric and qualitative thematic analysis findings. Subsequently, we revealed recent trends, context, theory, and nomological network in the domain, followed by the main themes and clusters, such as anthropomorphism, theory-based works, methodological foundations, service robots, and employee and customer views on service robots, and their relations with AI in T&H. The research also offers aresearch agenda that outlines opportunities for future AI studies.
Keywords: Artificial intelligence; service robots; tourism and hospitality; literature review; bibliometric analysis